Designing Teaching Materials English for Agribusiness Through Studentsâ Need Analysis - Donal, Andri; Ras, Fakhri; Rahayu, Pipit; Tarumun, Suardi; Gunawan, Ikhsan (Proceedings of the UR International Conference on Educational Sciences, 2018)
Teaching material is a complete elaboration of the main material written in the curriculum or syllabus. Choosing and developing teaching materials is a must that is done by teachers. So that learning is in accordance with the learning objectives to be achieved. Choosing teaching materials is not just about collecting teaching material, but it must fulfill what is needed by students so that an effective, systematic and interesting learning process will be created. Likewise for English for Specific Purposes class, teaching English at agribusiness major of the University of PasirPengaraianwas still has problem in providing suitable teaching material.The purpose of this research wereto describe Agribusiness studentsâ goals in learning English What do studentsâ needs toward English teaching material. This research implemented research and development research design with the respondent of 52 students. The result of research showed that most of students expected that they could master English vocabulary related to Agribusiness and they needed in English teaching material discusses more about specific vocabulary but less portion for grammar. In addition, they also need the teaching material covered four English skills.